DAMPAK JOB INVOLVEMENT TERHADAP JOB OUTCOMES: PERAN MEDIASI WORK ENGAGEMENT - Sjahruddin, Herman; Baso Rachim, Andi Farid; Bastian, Adi; Daswati, Detti; Massugianto, Massugianto; Putra, Rakhmat Zainuddin; Sitanggan, Tony (Universitas Riau Kepulauan, 2025)
This research aims to investigate the role of work engagement as a mediator in explaining the impact of job involvement on job outcomes. This quantitative research was conducted using the positivism paradigm with 105 Gen Z individuals working in the banking services sector in the cities of Makassar, Pare-pare, and Palopo in South Sulawesi Province. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM). Hypothesis testing provides evidence that job involvement has a positive and significant impact on work engagement and job outcomes. Additionally, work engagement also has a positive and significant effect on improving job outcomes. Job involvement can improve job outcomes through work engagement.